Radon emanation from polymetallic nodules from the CCZ collected during SONNE cruises SO239 and SO268/2 - Jessica B Volz; Walter Geibert; Dennis Koehler; Michiel M Rutgers van der Loeff; Sabine Kasten (PANGAEA, 2022)
This dataset comprises radon concentrations emanated from four polymetallic nodules of different sizes from the CCZ. The nodules were collected in the framework of the European collaborative JPI Oceans MiningImpact project onboard R/V SONNE cruises SO239 in 2015 and SO268 in 2019. Radon emanation was measured by enclosing the nodules in a glass chamber (volume = 2.02 L) while continuously circulating the gas in the system through a Rad7 device (Durrige Inc.), which is designed to measure specifically radon. As comparison, a 4.6 Bq Ra-226 standard was analyzed. The concentrations were evaluated with the Capture® software.